Lumps and bumps in the mouth and lips - Kalavrezos, Nicholas (Henry Stewart Talks, 2017)
Benign and malignant lesions of oral cavity and lips, Differential Diagnosis, Diagnosis of Oral Cancer: Aetiology, Classification, Principles of Management, Treatment and Outcomes